Relationship between workplace environments and employees’ productivity in Shah Alam City Council (MBSA) / Munira Izzatie Md Azman and Rabiah Md.Ramli - Md Azman, Munira Izzatie; Md.Ramli, Rabiah (Faculty of Business and Management, 2015)
Employee productivity can be defined as a level of efficiency of individual’s productions or output in their job performance. The purpose of this study is to investigate the relationship between workplace environments and employee’s productivity in Shah Alam City Council (MBSA). In this study only 63 respondents which are employees at Service Management Department selected using simple random sampling. The objectives of this study aims to investigate the level of employee productivity among Shah Alam City Council (MBSA’s) staff, to examine employee dominant working environment and employee productivity and to identify th relationship between workplace environment and employee productivity. Eventually, this research discovered that most of the respondents were age between 20-29 years old, female, married, most of them have a scale of household monthly income range between RM 2001- RM 3000, permanent staff, SPM level education and more than 3 years working there. Besides that, this study is a quantitative research study whereby the findings of the study were analysed by using the Statistical Package for the Social Science (SPSS) version 20.0. The data collected in this study is analysed by using frequency, descriptive analysis, reliability, Pearson’s correlation analysis and multiple regressions in order to achieved the research objectives. After the data have been analysed, the result showed that, there is a significance correlation between the communication factors with the employee’s productivity. This study also said to be beneficial to organization in order to increase the employee’s productivity. At the end of this research, some of the recommendations are also having been discussed.